Effects of a therapeutic exercise program in children with non-cystic fibrosis bronchiectasis: A pilot randomized controlled trial - Joschtel, Barbara; Gomersall, Sjaan R.; Tweedy, Sean; Petsky, Helen; Chang, Anne B.; Trost, Stewart G. (Frontiers in Pediatrics, 2022)
Background: In the absence of randomized controlled trials (RCTs) on the benefits of therapeutic exercise programs involving children with bronchiectasis, we undertook a pilot RCT to evaluate the effects of a play-based therapeutic exercise program on proficiency in fundamental movement skills (FMS) proficiency, cardiorespiratory fitness, perceived competence, and health-related quality of life (HR-QoL). Methods: Children (mean  SD age: 7.5  2.6 years) with bronchiectasis unrelated to cystic fibrosis were randomized to a 7-week therapeutic exercise program (n=11) or wait-list control (n=10). The exercise program comprised 7 x 60-minute weekly sessions and was supplemented by a home-based program 2-days/week. Participants were assessed on: FMS (locomotor and object control skills) using the TGMD-2; cardiovascular fitness by calculating the percent change in heart rate (%ΔHR) from rest to completion of the first stage of a submaximal treadmill test; perceived competence using Harter’s athletic competence subscale; and QoL with the PedsQL. Results: Significant group by time interactions were observed for locomotor and object control skills. Children completing the therapeutic exercise program exhibited significant improvements in both locomotor (pre 29.0 ± 2.0, post 35.2 ± 2.2, p=0.01) and object control (pre 27.0 ± 2.0, post 35.5 ± 2.2, p=0.01) skills, with no significant change in controls (pre 31.6 ± 2.1, post 31.8 ± 2.3 and pre 31.0 ± 2.1, post 32.3 ± 2.3, respectively). Among children completing the program, %ΔHR declined from 53% to 47%, while %ΔHR declined only marginally among controls (0.9%), but the group by time interaction was not statistically significant. The program had a small positive impact on competence perceptions (Cohen’s d=0.2) and HR-QoL (Cohen’s d=0.3). Conclusion: This pilot RCT provides preliminary evidence for the efficacy of a play-based therapeutic exercise program to improve proficiency in FMS and fitness in children with bronchiectasis. The results are sufficiently positive to warrant conducting a larger RCT testing the efficacy of the exercise program in children with bronchiectasis and/or other chronic respiratory conditions.